Penerapan Metode Mind Mapping Pada Pembelajaran Akidah Akhlak - Maula, Aris Rohmatul; Salsabila, Sari; Rusydiyah, Evi Fatimatur (LP2M Universitas Islam Ahmad Dahlan, 2024)
The teacher centered learning (TCL) learning approach is still one of the common problems often faced in Islamic Religious Education learning including the subject of akidah akhlak. In fact, since the implementation of the 2013 curriculum, the student centered learning (SCL) approach has been echoed but has not been fully realized until the implementation of the merdeka curriculum. Therefore, this study aims to analyze more deeply the application of the SCL approach to learning akidah akhlak which in this case utilizes the use of the mind mapping method in order to create active learning as expected by the merdeka curriculum. This research is a case study research that uses a qualitative approach with data collection techniques in the form of observation, interviews and documentation. And the data analysis technique is carried out by data condensation, data presentation, and ending with drawing conclusions. The results of this study indicate that the application of the mind mapping method in the subject of akidah and akhlak applied in MTs Tarbiyatut Tholabah class VIII female is effective in improving understanding, creativity, collaboration and making learning more enjoyable for students. In the regular home class shows a higher level of creativity and in the takhassush class shows aspects of active discussion and deep understanding.